The Resilience of Malay Silver Craft Design: sustaining cultural heritage and promoting sustainable industrialization - Syed Mohd Faisal Syed Ahmad,; Hanif Khairi,; Mohd Fauzi Kamarudin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This research paper investigates the traditional Malay silver craft that has existed for two centuries, reflecting the community's culture and heritage. The Srivijaya Kingdom and British colonial rule historically influenced this Malay culture's silver craft, encapsulating beliefs, dreams, and resilience. Originating in Kelantan, Malaysia, the Malay silver craft industry flourished, but recent studies reveal its decline and potential extinction. This paper's primary objective is to comprehensively identify and propose strategies for integrating sustainable practices of silver craft, aligning with the UN's Sustainable Development Goals (SDGs), focusing on sustainable industrialization and cultural heritage preservation. The research seeks to preserve and revitalize the craft industry for community benefit, emphasizing its socio-economic impact, potential for job creation, income generation, tourism, and intangible heritage preservation. The paper conducts a literature review, visual research, and focus group discussions employing anthropology, art history, and community development. This research emphasizes the importance of sustaining cultural heritage, fostering community resilience, and empowerment. Influenced by their cultural beliefs, environment, looking at nature, and the natural world, the fine silver craft undergoes artistic expression, subsequently fostering social cohesion and interaction. Following the quadruple helix concept, the Malay silver craft industry revival engaged through collaboration among local artisans, government agencies, community organizations, and academicians. By utilizing thematic analysis based on focus group discussion, this research thoroughly analyses the sustainability of the Malay silver craft domain, interpreting key thematic codes that underpin its ecological and socio-cultural significance within the framework of local craft in Malaysia.